Health education films in the twentieth century - Bonah, Christian 1965-; Cantor, David 1957-; Laukötter, Anja 1972- (Rochester studies in medical history, 2018)
"Examines the impact and importance of the health education film in Europe and North America in the first half of the twentieth century"...